Alterations of oral microbiota and cytokines profile in children and young adults with type 1 diabetes - Aldegheri, Luana; Catamo, Eulalia; Zanotta, Nunzia; Campisciano, Giuseppina; Cason, Carolina; Conti, Andrea; Cipullo, Chiara; Cadenaro, Milena; Tornese, Gianluca; Navarra, Chiara; Comar, Manola; Robino, Antonietta (Frontiers in Endocrinology, 2025)
IntroductionType 1 diabetes (T1D) is a chronic autoimmune disease caused by the destruction of pancreatic β cells. Although T1D is characterized by an increased susceptibility to oral inflammatory diseases, studies investigating the relationship between oral microbiota, oral inflammation, and T1D remain limited and often report conflicting results. MethodsIn this work, we compared both oral microbiota composition and cytokines profile of 75 children and young adults with T1D and 79 healthy controls (HC), using 16S rRNA gene targeted sequencing and magnetic bead-based multiplex immunoassays. ResultsWe found significant changes in both alpha and beta diversity, with a decrease in species richness (p-value<0.001) and an increase in species evenness (p-value<0.001). At the genus level, T1D participants exhibited a lower abundance of Fusobacterium (p-value<0.001) and a higher abundance of Atopobium and Prevotella (p-value=0.011 and p-value=0.022, respectively) compared to HC. Moreover, cytokines profile analysis showed lower levels of IFN-γ (p-value<0.001) and increased levels of IL-1β (p-value=0.01) in T1D compared to HC. An association between IL-1β levels and the abundance of Prevotella also emerged (p-value=0.001). DiscussionOverall, our findings suggest that in subjects with T1D changes in the oral microbiota composition may contribute to modify the immune response toward alteration of the cytokine profile.